2009
DOI: 10.4161/cc.8.6.7941
|View full text |Cite
|
Sign up to set email alerts
|

A novel form of the telomere-associated protein TIN2 localizes to the nuclear matrix

Abstract: Telomeres are specialized heterochromatin at the ends of linear chromosomes. Telomeres are crucial for maintaining genome stability and play important roles in cellular senescence and tumor biology. Six core proteins-TRF1, TRF2, TIN2, POT1, TPP1 and Rap1 (termed the telosome or shelterin complex)-regulate telomere structure and function. One of these proteins, TIN2, regulates telomere length and structure indirectly by interacting with TRF1, TRF2 and TPP1, but no direct function has been attributed to TIN2. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 50 publications
(94 reference statements)
3
42
0
Order By: Relevance
“…Through sequential extraction of the nuclear matrix, we have shown that the nuclear matrix contains a small amount of endogenous TRF1, TRF2 and hRap1, suggesting that components of the shelterin complex are associated with the nuclear matrix, in agreement with previous reports [10, 17]. We have previously estimated that about 1-5% of endogenous TRF2 is methylated by PRMT1 [29].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Through sequential extraction of the nuclear matrix, we have shown that the nuclear matrix contains a small amount of endogenous TRF1, TRF2 and hRap1, suggesting that components of the shelterin complex are associated with the nuclear matrix, in agreement with previous reports [10, 17]. We have previously estimated that about 1-5% of endogenous TRF2 is methylated by PRMT1 [29].…”
Section: Discussionsupporting
confidence: 91%
“…Mammalian telomeric DNA consists of tandem repeats of TTAGGG and is bound by a six-subunit protein complex [13, 14], referred to as shelterin or telosome, which is composed of TRF1, TRF2, TIN2, POT1, TPP1 and hRap1. Telomeres are attached to the nuclear matrix [15, 16] and components of the shelterin complex have been reported to be associated with the nuclear envelope as well as the nuclear matrix [10, 17-19]. TIN2L, an isoform of TIN2, has been suggested to mediate the interaction between telomeres and the nuclear matrix [17] whereas hRap1 has been implicated in tethering telomeres to the nuclear envelope [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunoblot analysis indicated efficient depletion of TIN2 (64% knockdown) and TIN2L (75% knockdown; a higher-molecular-weight TIN2 isoform) ( Fig. 2H; Kaminker et al 2009). FISH analysis of TIN2-depleted vector control cells revealed a dramatic loss in sister telomere cohesion (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…TIN2 also functions in sister telomere cohesion, and secondarily in telomere break repair, via its interaction with the cohesin subunit SA1 [70, 71]. Lastly, two isoforms of TIN2 are expressed in human cells, including a longer isoform, known as TIN2L, which is formed by the inclusion of three C-terminal exons through alternative splicing [72]. While both isoforms appear to bind similarly to TRF1, TRF2, and TPP1, TIN2L has been shown to a have greater association with the nuclear matrix and telomeres.…”
Section: Sporadic (De Novo) Autosomal Dominant Dc: Tinf2mentioning
confidence: 99%